Pelatihan Pencatatan Keuangan Sederhana Berbasis Aplikasi Digital bagi UMKM Paroki Redemptor Mundi Surabaya - Mahsina Mahsina; Agustinus Winoto; Rudiana Fibriani; Rosy Aprieza Puspita Zandra (Senarai Kearifan Lokal Akuntansi: Jurnal Pengabdian Masyarakat, 2026)
This community service activity was motivated by the low level of understanding among Micro, Small, and Medium Enterprises (MSMEs) assisted by the PSE of Redemptor Mundi Parish in Surabaya in recording their business finances. Many of these businesses do not yet have a proper bookkeeping system, still mix personal and business finances, or do not know how to prepare simple financial statements. The purpose of this activity was to improve the knowledge and skills of MSME actors in financial recording using simple digital applications. A participatory and educational approach was applied through several stages, including preparation, socialization and training, mentoring in preparing financial statements, and evaluation. The results of this activity show that participants gained a better understanding of how to record transactions, separate personal and business finances, and prepare simple income statements and cash flow reports. This program greatly assisted MSMEs assisted by the PSE of Redemptor Mundi Parish Surabaya in preparing financial reports independently. The activity also increased awareness of accountability and financial transparency, while supporting the sustainability and competitiveness of MSME.